Carbon storage on an Oxisol fertilized with pig slurry and cropped under no-tillage Acúmulo de carbono em Latossolo adubado com dejeto líquido de suínos e cultivado em plantio direto - Mafra M.S.H.* (2014)
The objective of this work was to estimate organic C storage rates in an Typic Hapludox fertilized with soluble fertilizer and pig slurry and cropped under no tillage. The experiment was carried out in the municipality of Campos Novos, in the state of Santa Catarina, Brazil, and the following treatments were applied annually: no fertilization; soluble fertilizer; 25 m3 ha-1 pig slurry + soluble fertilizer; and rates of 25, 50, 100, and 200 m3 ha1 pig slurry. The following were determined: organic carbon (OC) stocks in the 0-20 cm soil layer; C inputs by crop biomass and pig slurry; annual C fxation rates; and the soil OC humifcation (k1) and mineralization (k2) coeffcients. The real and apparent C fxation rates increased according to pig slurry rates, ranging from 0.6 to 1.7 and from 0.05 to 1.0 Mg ha-1 per year, respectively. The k1 and k2 coeffcients were 0.17 and 0.011, respectively, whereas the C input required to maintain the initial stock of OC is of 4.14 Mg ha 1 per year. Pig slurry applied annually on a Typic Hapludox cropped with the maize black oat succession under no tillage increases soil OC in rates of up to 200 m3 ha-1.